2010
DOI: 10.1590/s1415-47572010005000086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common α-thalassemia determinants in south Brazil: importance for the diagnosis of microcytic anemia

Abstract: Alpha thalassemia has not been systematically investigated in Brazil. In this study, 493 unrelated individuals from the southernmost Brazilian state of Rio Grande do Sul were screened for deletional forms of α-thalassemia. One hundred and one individuals had microcytic anemia (MCV < 80 fL) and a normal hemoglobin pattern (Hb A 2 < 3.5% and Hb F < 1%). The subjects were screened for - α3.7 , - α4.2 , - α20.5 , — SEA and — MED deletions but only the - α3.7 allele was detected. The - α3.7 allele frequency in Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
7
14
0
Order By: Relevance
“…Although the frequency of 3.7 kb deletion (8.5%) was similar to that observed in Afro-newborns from Salvador, Bahia (11.0%) (Adorno et al , 2008), as well as Afro-descendants from Campinas, São Paulo (13.0%) (Sonati et al , 1991) and Porto Alegre, Rio Grande do Sul (12.0%) (Wagner et al , 2010), it was higher than the frequency found in Euro-descendants from Porto Alegre (2.0%) (Wagner et al , 2010) and individuals from the urban area of Santarém, PA (3.3%) (Souza et al , 2009). Gene flow from local non-Afro-individuals was placed in evidence by the occurrence of - - (MED) deletion (1.2%), a common mutation in Mediterraneans (Higgs and Weatherall, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…Although the frequency of 3.7 kb deletion (8.5%) was similar to that observed in Afro-newborns from Salvador, Bahia (11.0%) (Adorno et al , 2008), as well as Afro-descendants from Campinas, São Paulo (13.0%) (Sonati et al , 1991) and Porto Alegre, Rio Grande do Sul (12.0%) (Wagner et al , 2010), it was higher than the frequency found in Euro-descendants from Porto Alegre (2.0%) (Wagner et al , 2010) and individuals from the urban area of Santarém, PA (3.3%) (Souza et al , 2009). Gene flow from local non-Afro-individuals was placed in evidence by the occurrence of - - (MED) deletion (1.2%), a common mutation in Mediterraneans (Higgs and Weatherall, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…This was previously reported [14], where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia [20][21][22][23][24][25][26][27], while others [14,28] reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. Unlike many other similar studies that have examined the red cell indices in alpha thalassaemia, present cohort showed significantly lower MCV (52-53 fL) giving an impression of additional pathology.…”
Section: Discussionsupporting
confidence: 92%
“…When we analyzed the sub-sample with African ancestry, the α −3.7 mutation carrier frequency increased and was 6.5% higher than that for the whole sample but, as expected from the admixture, was lower than that observed in parental African populations, where the frequency of α-thalassemia carriers ranges from 11% to 50% (Weatherall and Clegg, 2001). The α −3.7 mutation carrier frequency in the sub-sample with African ancestry was also lower than that observed in Afro-Brazilian populations, where the carrier frequency ranges from 7% to 21% (Sonati et al , 2001; Adorno et al , 2005; Souza et al , 2009; Wagner et al , 2010), possibly because of a higher non-African admixture in this Afro-Uruguayan population. The α-thalassemia frequencies for Afro-descendants with microcytosis (33.3%) and the group of children with microcytosis and hypochromia (32.3%) were both similar to the frequency observed in a similar sample from the southern Brazilian state of Rio Grande do Sul (31.7%) (Wagner et al , 2010) and lower than that observed for a population in southeastern Brazil in which α-thalassemia explained about 50% of the cases of microcytosis (Borges et al , 2001).…”
Section: Discussionmentioning
confidence: 54%